The Relationship between the Quality of the Physical Environment of the House and the Incidence of Pulmonary Tuberculosis in Tangerang City in 2022 - Hanung Nurany; Mursid Raharjo; Mateus Sakundarno Adi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Tuberculosis is an infectious disease that is a major health problem and one of the leading causes of death in the world. This study aimed to determine whether there is a relationship between the physical condition of the house and the incidence of pulmonary tuberculosis in Tangerang City, Banten Province. This research is a quantitative research with a case control design. This study was conducted in Tangerang City conducted from June to September 2022. The sample for this study was 400 people, consisting of 200 case samples and 200 control samples. The sampling technique used in this research is proportional sampling technique. Data analysis in this study was analysis using the Chi square test and the Odds Ratio value. The research results show that there is a relationship between occupancy density and the incidence of pulmonary tuberculosis with (p value = 0.001; OR= 4,397; 95% CI=2,454-7,879), there is a relationship between occupancy density and the incidence of pulmonary tuberculosis with a value of (p value=0,001; OR=2,970; 95% CI=1,968-4,482), there is no relationship between occupancy density and the incidence of pulmonary tuberculosis with a (p value=0.679; OR=0,858; 95% CI=0,499–1,476), there is a relationship between occupancy density and the incidence of pulmonary tuberculosis with a (p value =0.001; OR=6,791; 95% CI=4,382–10,523), there is no relationship between occupancy density and the incidence of pulmonary tuberculosis with a (p value=0.764; OR=0,874; 95% CI =0,485–1,574); there is no relationship between occupancy density and the incidence of pulmonary TB with a (p value=0.471; OR=1,225; 95% CI=0,764–1,964).in the Tangerang City area. The advice that can be given is that patients pay more attention to the house physical condition so that no proliferation of mycobacterium tuberculosis can be transmitted to other people and people in the house.Keyword: Tuberculosis, Physical Environment, Environmental Factors